The organisation and delivery of health improvement in general practice and primary care: a scoping study - Stephen Peckham; Jane Falconer; Steve Gillam; Alison Hann; Sally Kendall; Kiran Nanchahal; Benjamin Ritchie; Rebecca Rogers; Andrew Wallace (National Institute for Health Research, 2015)
Background: This project examines the organisation and delivery of health improvement activities by and within general practice and the primary health-care team. The project was designed to examine who delivers these interventions, where they are located, what approaches are developed in practices, how individual practices and the primary health-care team organise such public health activities, and how these contribute to health improvement. Our focus was on health promotion and ill-health prevention activities. Aims: The aim of this scoping exercise was to identify the current extent of knowledge about the health improvement activities in general practice and the wider primary health-care team. The key objectives were to provide an overview of the range and type of health improvement activities, identify gaps in knowledge and areas for further empirical research. Our specific research objectives were to map the range and type of health improvement activity undertaken by general practice staff and the primary health-care team based within general practice; to scope the literature on health improvement in general practice or undertaken by health-care staff based in general practice and identify gaps in the evidence base; to synthesise the literature and identify effective approaches to the delivery and organisation of health improvement interventions in a general practice setting; and to identify the priority areas for research as defined by those working in general practice. Methods: We undertook a comprehensive search of the literature. We followed a staged selection process involving reviews of titles and abstracts. This resulted in the identification of 1140 papers for data extraction, with 658 of these papers selected for inclusion in the review, of which 347 were included in the evidence synthesis. We also undertook 45 individual and two group interviews with primary health-care staff. Findings: Many of the research studies reviewed had some details about the type, process or location, or who provided the intervention. Generally, however, little attention is paid in the literature to examining the impact of the organisational context on the way services are delivered or how this affects the effectiveness of health improvement interventions in general practice. We found that the focus of attention is mainly on individual prevention approaches, with practices engaging in both primary and secondary prevention. The range of activities suggests that general practitioners do not take a population approach but focus on individual patients. However, it is clear that many general practitioners see health promotion as an integral part of practice, whether as individual approaches to primary or secondary health improvement or as a practice-based approach to improving the health of their patients. Our key conclusion is that there is currently insufficient good evidence to support many of the health improvement interventions undertaken in general practice and primary care more widely. Future Research: Future research on health improvement in general practice and by the primary health-care team needs to move beyond clinical research to include delivery systems and be conducted in a primary care setting. More research needs to examine areas where there are chronic disease burdens - cancer, dementia and other disabilities of old age. Reviews should be commissioned that examine the whole prevention pathway for health problems that are managed within primary care drawing together research from general practice, pharmacy, community engagement, etc. Funding: The National Institute for Health Research Health Services and Delivery Research programme.